Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To verify that [tex]\( g(x) \)[/tex] is the inverse of [tex]\( f(x) \)[/tex], we need to show that [tex]\( f(g(x)) = x \)[/tex] and [tex]\( g(f(x)) = x \)[/tex].
First, let's find [tex]\( f(g(x)) \)[/tex]:
1. Start with the function [tex]\( g(x) = \frac{1}{5} x + 5 \)[/tex].
2. Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{1}{5} x + 5\right) \][/tex]
3. Recall the function [tex]\( f(x) = 5x - 25 \)[/tex]:
[tex]\[ f\left(\frac{1}{5} x + 5\right) = 5\left(\frac{1}{5} x + 5\right) - 25 \][/tex]
4. Simplify the expression inside [tex]\( f(x) \)[/tex]:
[tex]\[ = 5 \cdot \frac{1}{5} x + 5 \cdot 5 - 25 = x + 25 - 25 = x \][/tex]
This verifies that [tex]\( f(g(x)) = x \)[/tex].
Next, let's find [tex]\( g(f(x)) \)[/tex]:
1. Start with the function [tex]\( f(x) = 5x - 25 \)[/tex].
2. Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g(f(x)) = g(5x - 25) \][/tex]
3. Recall the function [tex]\( g(x) = \frac{1}{5} x + 5 \)[/tex]:
[tex]\[ g(5x - 25) = \frac{1}{5}(5x - 25) + 5 \][/tex]
4. Simplify the expression inside [tex]\( g(x) \)[/tex]:
[tex]\[ = \frac{1}{5} \cdot 5x - \frac{1}{5} \cdot 25 + 5 = x - 5 + 5 = x \][/tex]
This verifies that [tex]\( g(f(x)) = x \)[/tex].
Therefore, both [tex]\( f(g(x)) = x \)[/tex] and [tex]\( g(f(x)) = x \)[/tex] are satisfied, confirming that [tex]\( g(x) \)[/tex] is the inverse of [tex]\( f(x) \)[/tex].
Among the provided expressions,
- [tex]\(\frac{1}{5}(5 x - 25) + 5\)[/tex] simplifies to [tex]\( x \)[/tex], which correctly represents [tex]\( g(f(x)) \)[/tex].
Therefore, the correct expression to verify that [tex]\( g(x) \)[/tex] is the inverse of [tex]\( f(x) \)[/tex] is:
[tex]\[ \frac{1}{5}(5 x - 25) + 5 \][/tex]
So, the answer is:
[tex]\[ \boxed{\frac{1}{5}(5 x - 25) + 5} \][/tex]
First, let's find [tex]\( f(g(x)) \)[/tex]:
1. Start with the function [tex]\( g(x) = \frac{1}{5} x + 5 \)[/tex].
2. Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(x)) = f\left(\frac{1}{5} x + 5\right) \][/tex]
3. Recall the function [tex]\( f(x) = 5x - 25 \)[/tex]:
[tex]\[ f\left(\frac{1}{5} x + 5\right) = 5\left(\frac{1}{5} x + 5\right) - 25 \][/tex]
4. Simplify the expression inside [tex]\( f(x) \)[/tex]:
[tex]\[ = 5 \cdot \frac{1}{5} x + 5 \cdot 5 - 25 = x + 25 - 25 = x \][/tex]
This verifies that [tex]\( f(g(x)) = x \)[/tex].
Next, let's find [tex]\( g(f(x)) \)[/tex]:
1. Start with the function [tex]\( f(x) = 5x - 25 \)[/tex].
2. Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g(f(x)) = g(5x - 25) \][/tex]
3. Recall the function [tex]\( g(x) = \frac{1}{5} x + 5 \)[/tex]:
[tex]\[ g(5x - 25) = \frac{1}{5}(5x - 25) + 5 \][/tex]
4. Simplify the expression inside [tex]\( g(x) \)[/tex]:
[tex]\[ = \frac{1}{5} \cdot 5x - \frac{1}{5} \cdot 25 + 5 = x - 5 + 5 = x \][/tex]
This verifies that [tex]\( g(f(x)) = x \)[/tex].
Therefore, both [tex]\( f(g(x)) = x \)[/tex] and [tex]\( g(f(x)) = x \)[/tex] are satisfied, confirming that [tex]\( g(x) \)[/tex] is the inverse of [tex]\( f(x) \)[/tex].
Among the provided expressions,
- [tex]\(\frac{1}{5}(5 x - 25) + 5\)[/tex] simplifies to [tex]\( x \)[/tex], which correctly represents [tex]\( g(f(x)) \)[/tex].
Therefore, the correct expression to verify that [tex]\( g(x) \)[/tex] is the inverse of [tex]\( f(x) \)[/tex] is:
[tex]\[ \frac{1}{5}(5 x - 25) + 5 \][/tex]
So, the answer is:
[tex]\[ \boxed{\frac{1}{5}(5 x - 25) + 5} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.